Diversity and Structure of Bacterial Communities in the Gut of Spider: Thomisidae and Oxyopidae - Kumar, Vikas; Tyagi, Inderjeet; Tyagi, Kaomud; Chandra, Kailash (Frontiers in Ecology and Evolution, 2020)
The gut microbiomes of insects were known to have great impact on their physiological properties for survival like nutrition, behaviour and health. In nature, spiders are one of the main predators of insects and yet their gut microbiomes remain unclear. It is important to explore the gut microbiomes of spiders in the wild to gain an insight on the host-bacterial relationship. Here, we studied the diversity and structure of gut bacterial communities of seven spider species belonging to two families i.e. Thomisidae and Oxyopidae from different states of India. Our data revealed a total of 16 bacterial phyla with Proteobacteria as predominant group in Thomisidae and Firmicutes in Oxyopidae.The core bacterial communities in the spider guts include the genera of Acinetobacter, Staphylococcus, Corynebacterium, Cutibacterium, and Pseudomonas. The genus Paraclostridium was observed for the first time and only in one spider species i.e. Peucetia viridans. Our data also indicated a higher gut bacterial community similarity between spider species belonging to Thomisidae as compared to those belonging to Oxyopidae. Furthermore, PICRUSt2 analysis predicted the presence of nine active functional metabolic pathways related to the metabolism of fatty acids and sugar, degradation of organic compounds, and biosynthesis of vitamin E.